Diagnostic imaging of a Rare Intraosseous Mandibular Schwannoma using Cone Beam Computed Tomography – A case report - Kuduva Ramesh, Shilpa Shree; Jayachandran, Sadaksharam (Indian Journal of Case Reports, 2020)
Intraosseous schwannoma is a very rare (